OSI AND TCP/IP REFERENCE MODELS IN ISLAMIC DEVELOPMENT AND THOUGHT AND THE HISTORY OF DISCOVERY IN THE HEYDAY OF ISLAM - Eka Ramdan Permana; Fajar Nugraha Wahyu; Handri Taufik; Thoyyibah T (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
In the development of information technology, the reference model of OSI (Open Systems Interconnection) and TCP / IP (Transmission Control Protocol / Internet Protocol) has become the main foundation in the design and implementation of computer networks. However, the relationship between these models and Islamic thought and the history of discovery in the heyday of Islam has not been discussed in much depth. In this journal, we examine both reference models and relate them to Islamic thought and the history of discovery in the heyday of Islam. We highlight concepts in the OSI and TCP/IP models that may have relevance to values, principles, or scholarly contributions established by Muslim scholars in the past. also reviews how these models can provide inspiration in developing contemporary Islamic thought, especially in the context of information and communication technology. In addition, we discuss the history of inventions in the heyday of Islam to provide an in-depth historical context related to the development of modern information technology. It is expected to contribute to the understanding of the relationship between Islamic thought and modern information technology, as well as stimulate further discussion and research in this field.